Peran Dinas Sosial Dalam Merehabilitas Anak Korban Kekerasan Seksual Di Kota Muaradua Kabupaten OKU Selatan - Alexander Alexander; Neni Noviza; Hartika Utami Fitri (ScidacPlus, 2023)
The role of the Social Service in dealing with child victims of sexual violence in South Oku Regency. The problem discussed in this research is what methods are used by the Social Service to rehabilitate child victims of sexual violence in the city of Muaradua, South Oku Regency? And what is the role of the Social Service in rehabilitating child victims of sexual violence in Muaradua City, South Oku Regency? The main aim of this research is to determine and analyze the role of the Social Service in rehabilitating child sexual victims in Muaradua City, South Oku Regency. The research findings are: First, the method used by the Social Service to rehabilitate child victims of sexual violence who are under its protection is by taking two approaches, namely (a). Religious spiritual approach, in a religious spiritual approach it will give birth to peace of mind, and (2). Motivational approach, this is done to give birth to a spirit of life in humans. Second, the role of the Social Service in rehabilitating child victims of sexual violence includes providing anti-sexual violence outreach to children from the family level to the community, providing assistance to victims of sexual violence both legally and providing assistance in recovering from the trauma that occurred to the victim.